IMPACT OF LOCKDOWN DUE TO COVID-19 OUTBREAK ON MUSCULOSKELETAL HEALTH IN GAZA’S UNIVERSITY STUDENTS. ACROSS-SECTIONAL STUDY - Osama Alshana; Mosab Aldabbas (Scholar Express Journals, 2022)
Background: Coronavirus pandemic disease has reached to around 216 countries, with approximately 11,475,598 currently infected cases and 1,193,912 deaths globally as of October 31, 2020. Because of that many countries have implemented lockdown to slow down the spread of COVID-19 those results in a wide variety of symptoms. This article aimed to evaluate the impacts of lockdown due to COVID-19 on musculoskeletal health among university students in Palestine.This study aims to investigate the relationship between lock-down due to covid19 and other problems such as musculoskeletal problem, sleep quality, joints or muscles symptoms, and overall impact in Gaza’s university students. Method: In view of the Movement Control Order (MCO) or Lockdown by Palestine authority amid COVID-19, an online survey via Google form was conducted. Three hundred students from different universities and colleges participated in E-survey. The survey was conducted by sending a connection to Google Forms for musculoskeletal health questionnaire through social networking sites using google forum to conduct the effect during the entire lockdown. Result: During the period of COVID-19 lockdown, there was a statistically increase in the musculoskeletal symptoms compared to before (P <0.05), like moderate pain during the day (44%), needing help from others (18.5%), males over females regarding joint or muscles problem during work daily (35%), while, moderate to severe troubles during sleep (37.4%, 23.8%) respectively.
Keywords: Musculoskeletal symptoms; covid-19 lockdown; university students; night sleep troubles